Ultrastructural Remodeling of the Blood–Brain Barrier and Neurovascular Unit by Lipopolysaccharide-Induced Neuroinflammation - Erickson, M. A.; Shulyatnikova, T. O.; Banks, W. A.; Hayden, M. R.; Шулятнікова, Тетяна Володимирівна (My University, 2023)
Abstract: The blood–brain barrier (BBB) is an interface primarily comprised of brain endothelial cells (BECs), separating the central nervous system (CNS) from the systemic circulation while carefully regulating the transport of molecules and inflammatory cells, and maintaining the required steady-state environment. Inflammation modulates many BBB functions, but the ultrastructural cytoarchitectural changes of the BBB with inflammation are understudied. Inflammation was induced in male 8–10-week-old CD-1 mice with intraperitoneal lipopolysaccharide (LPS), using a regimen (3 mg/kg at 0, 6, and 24 h) that caused robust BBB disruption but had minimal lethality at the study timepoint of 28 h. Perfusion-fixed brains were collected and the frontal cortical layer III regions were analyzed using a transmission electron microscopy (TEM). The LPS-treated mice had pronounced ultrastructural remodeling changes in BECs that included plasma membrane ruffling, increased numbers of extracellular microvesicles, small exosome formation, aberrant BEC mitochondria, increased BEC transcytosis, while tight junctions appeared to be unaltered. Aberrant pericytes were contracted with rounded nuclei and a loss of their elongated cytoplasmic processes. Surveilling microglial cells were attracted to the neurovascular unit (NVU) of BECs, and astrocyte detachment and separation were associated with the formation of a perivascular space and pericapillary edema. The LPS treatment resulted in numerous ultrastructural aberrant remodeling changes to the neurovascular unit’s BECs, microglia, pericytes, and astrocytes. In summary, a disturbance of the NVU morphology is a consequence of LPS treatment.
Keywords: blood–brain barrier; brain endothelial cells; caveolae-mediated vesicles; clathrin-mediated vesicles; macropinosomes; microglia; neurovascular unit; receptor-mediated transcytosis; transcytosis; transmission electron microscopy